Analisis Pendapatan Usahatani Padi Sehat Dan Padi Non Sehat Di Kampung Rejo Asri Kecamatan Seputih Raman Kabupaten Lampung Tengah - Sefti Mulya Sari; Ainul Mardliyah (JURNAL WACANA PERTANIAN, 2020)
This study aims to analyze the comparison of the income levels of healthy and non-healthy rice farmers in the study area. This research used simple random sampling method. The research was conducted in Rejo Asri Village, Seputih Raman District, Central Lampung Regency with 75 healthy rice respondents and 88 non-healthy rice farmers as respondents. The analytical method used in this study used the income analysis method to determine the loss or loss of farming and the t test analysis method (different). The results showed that the production of healthy rice was 1,609.24 kg with an income of Rp. 6,430,408.67 / farm while non-healthy rice production was 3,477.18 kg with an income of Rp. 12,663,991.48 / farm. The result of different test (tcount) is -6.646 and significantly different with a probability of 0.000 less than 0.005, so Ho is rejected and Ha is accepted, meaning that the income of healthy rice farming is greater than the income of non-healthy rice farming.